Investigation of human infection with H5N6 avian influenza cases in Sichuan Province from 2014 to 2024: a retrospective study - Zhou, Lijun; Li, Zhirui; Zhou, Xingyu; Zhao, Lin; Peng, Huanwen; Du, Xunbo; Yang, Jianping; Hu, Fengmiao; Dong, Shuang; Li, Baisong; Liu, Guidan; Tang, Hongyu; et al. (Frontiers in Public Health, 2025)
ObjectiveThe objective is to examine the epidemiology and clinical features of human cases infected with H5N6 avian influenza in Sichuan Province from 2014 to 2024, and to offer guidance for the prevention and management of human infections with H5N6 avian influenza.MethodsEpidemiological survey reports of H5N6 avian influenza cases in Sichuan Province from 2014 to 2024 were compiled, and the epidemiological context and characteristics of 16 human cases infected with H5N6 avian influenza in the province were summarized and analyzed using descriptive epidemiological methods.ResultsFrom 2014, when the initial human case ofH5N6 infection was documented in Sichuan Province, to 2024, there have been 16 human cases of H5N6 avian influenza in the region, resulting in 12 fatalities and a case fatality rate of 75%. The instances were predominantly located in the Chengdu Plain, eastern Sichuan, and southern Sichuan.ConclusionHuman instances of H5N6 avian influenza in Sichuan Province exhibit no discernible periodicity, and entail significant fatality rates. It is essential to enhance the early diagnosis and treatment of avian influenza cases in medical facilities, prioritize farmers with preexisting conditions who have been in contact with deceased poultry, conduct influenza virus testing promptly, and administer antiviral medications at the earliest opportunity. Simultaneously, we must effectively engage in public awareness and education for the populace, manage poultry scientifically, and prevent direct contact with deceased poultries.